The Role of Social Functioning Between Vitality and Mental Distress in Hypertension: A Partial Mediation Model - Sara Guidotti; Francesca Giordano; Carlo Pruneti (European Journal of Investigation in Health, Psychology and Education)
(1) Background: Patients with hypertension face a relevant reduction in health-related quality of life. Specifically, the vitality domain is significantly impaired. This research aims to explore the association between quality of life and mental distress in patients with hypertension, explicitly emphasizing the mediating factor of social functioning above vitality. (2) Methods: This observational study consecutively recruited a hundred hypertensive patients (49% were males and 51% were females) aged between 23 and 82 years old (Mage = 56.04, SDage = 12.04). The Symptom Checklist-90-Revised (SCL-90-R) and the 36-Item Short Form Health Survey (SF-36) were administered to assess mental distress and quality of life, respectively. Two biological measures (i.e., cortisol levels and heart rate) were also collected. (3) Results: In total, 50% of participants indicated higher mental distress and reduced quality of life. Correlation analyses demonstrate various negative relationships between clinical features. Moreover, positive associations were found between mental distress and vitality and between vitality and physical and social functioning along with heart rate. Notably, it was determined that vitality negatively predicted mental distress directly and indirectly by mediating social functioning. (4) Conclusions: Despite these promising findings, this study’s cross-sectional nature does not allow for the definition of the causal relationship between the investigated variables. These results emphasize the importance of a comprehensive and multidisciplinary evaluation in understanding hypertensive patients’ psychophysical well-being and lifestyles, which social support may significantly modulate.